INDIVIDUAL EDUCATIONAL PATH BASED ON LEARNING STYLES THEORY AS A WAY TO REACH SUSTAINABLE QUALITY EDUCATION GOALS - G. Artyushina, Galina; L. Zhurbenko, Natalia; A.Sheypak, Olga (Revista Inclusiones, 2020)
Following the goals of sustainable development in the sphere of teaching professionally oriented foreign languages, the paper presents the results of the long term research aimed at collecting data about particularities of students representing different generations necessary for changing the system of professionally oriented foreign language teaching in non-linguistic technical universities in order to increase the efficiency of teaching specialists using a foreign language in professional activities and reach the aim of quality education for future generations. The research was carried out twice in 2012 and in 2019 on the basis of Howard Gardner’s multiple intelligence theory. The paper analyses the difference in learning styles of two generations of students showing the difference explained by constantly changing social environment. The collected data proved the necessity of changing the training contents and training approaches, introducing technologies and promoting learners autonomy. Often student-oriented approach is understood as a possibility of choosing teaching materials depending on the level of proficiency; we offered an approach of choose teaching “tools” depending on individual characteristics of every student to reach the most efficient resultswithin the student’s personal educational pathway.